Why national development experts are not included in development policy‐making and practice: The case of Ghana. (19th January 2023) - Kamruzzaman, Palash; Kumi, Emmanuel
Summary: Motivation: This article contributes to the debate around understanding whether and how the identity of aid workers (e.g. nationality, race, etc.) can contribute to inequality within various aid relationships. As "decolonizing development" is often employed either as a slogan or genuine goal, it is imperative that the politics of exclusion among/within development experts is critically scrutinized. Purpose: This article explores the processes of and the motivations behind how national development experts (NDEs) are frequently excluded in development policy‐making and practice in Ghana. Methods and approach: This article relies on qualitative research methods and draws from semi‐structured interviews conducted in two phases in 2017 and 2018 in Ghana. We focus on the narratives of the NDEs in Ghana who are perceived to be well placed to elucidate different mechanics of exclusionary processes and practice. Findings: International development experts (IDEs) are able to set agendas and exercise development decision‐making power as their governments or organizations provide funding for many development projects. This allows IDEs to influence development policies and practices in a way that eventually excludes the NDEs from development policy‐making in Ghana. We also reveal internal competition and power relations between NDEs and local actors (i.e. bureaucrats and politicians) can also exclude the NDEs from development policy‐making processes, a feature that is non‐existent in current scholarship. Policy implications: The exclusion of NDEs from national development decision‐making processes undermines efforts to promote national ownership. It is important to adopt a holistic approach that does not just focus on one particular aspect (e.g. power inequality among different actors) of exclusionary practice in international development but also looks into local political‐cultural settings as well as possible internal competition for resources.